Savoring alternative food : school gardens, healthy eating and visceral difference - Hayes-Conroy, Jessica (London : Routledge, 2014)
'Advocates of the alternative food movement often insist that food is our'common ground'--that through the very basic human need to eat, we all become entwined in a network of mutual solidarity. In this challenging book, the author explores the contradictions and shortcomings of alternative food activism by examining specific endeavours of the movement through various lenses of social difference--including class, race, gender, and age. While the solidarity adage has inspired many, it is shown that this has also had the unfortunate effect of promoting sameness over difference, eschewing inequities in an effort to focus on being'together at the table'. The author explores questions of who belongs at the table of alternative food, and who gets to decide what is eaten there; and what is at stake when alternative food practices become the model for what is right to eat? Case studies are presented based on fieldwork in two distinct loci of alternative food organizing: school gardens and slow food movements in Berkeley, California and rural Nova Scotia. The stories take social difference as a starting point, but they also focus specifically on the complexities of sensory experience--how material bodies take up social difference, both confirming and disrupting it, in the visceral processes of eating. Overall the book demonstrates the importance of moving beyond a promotion of universal'shoulds' of eating, and towards a practice of food activism that is more sensitive to issues of social and material difference'--
'In this challenging book, the author explores the contradictions and shortcomings of alternative food activism by examining specific endeavours of the movement through various lenses of social difference--including class, race, gender, and age'--
Includes bibliographical references and index.
Keywords: Food habits -- Social aspects; Nutrition -- Social aspects; Local foods -- Social aspects; Sustainable agriculture -- Social aspects